Strategi Dinas Pemuda, Olahraga dan Pariwisata Dalam Mengembangkan Sektor Pariwisata di Kota Bontang - Taufik Hidayatullah; Muhammad Noor; Letizia Dyastari (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
This research aims to look at the Strategy of the Department of Youth, Sports and Tourism in Improving the Tourism Zone, the information obtained from the original source is all parties who know about the subject to be studied in the form of words or activities from informants with the results of observations, interviews and documentation. The research results state that the system of the Division of Youth, Sports and Tourism in the Development of Travel Industrial Areas is still not ideal. (1) Accessibility of human resources at the Youth, Sports and Tourism Office of Bontang City has so far not been increased in number. (2) Limited assets for fostering the tourism travel industry in Bontang City are not many, so travel industry goods are also limited. (3) The current framework for vacation spots in Bontang City must actually be shifted. Especially those related to offices and important frameworks needed by guests such as electricity, latrines, clean water, housing, and others. (4) The technique used in creating a tourism travel industry in Bontang City is to make the closest guidelines or guidelines to the tourism travel industry. The real fix includes working on basic frameworks and offices. organized a Travel Industry Mindfulness Training which was attended by the Taman City community, travel business people and several travel industry Alert Gathering (Pokdarwis) events.